Immunoadjuvant Nanoparticles as Trojan Horses for Enhanced Photo-Immunotherapy in the Treatment of Triple-Negative Breast Cancer - Wu, Jinxian; Wang, Shanyong; Liu, Shanshan; Liu, Fang; Zhou, Feifan (Frontiers in Pharmacology, 2022)
Treatment of triple-negative breast cancer (TNBC) is faced with great challenges due to high invasiveness and poor prognosis. Therefore, effective treatment methods are urgently needed to both control primary tumors and suppress distant tumors. Herein, we employed glycated chitosan (GC), a polysaccharide macromolecular immunoadjuvant, to construct a self-assembly GC@ICG nanoparticles which is accessible to tumor cells for synergistic cancer treatment based on the combination of phototherapy and immunotherapy. In this strategy, the self-associated synthesis of spherical GC@ICG significantly improved the stability of ICG, and endowed GC with Trojan Horses in tumor cells for the enhancement of tumor immunogenicity. A bilateral 4T1 tumor-bearing mice model was established to evaluate the therapeutic outcomes and specific host antitumor immune response. Finally, GC@ICG based phototherapy can directly eliminate primary tumors and resist the progression of untreated distant tumors. Besides, compared to the treatment of L + GC + ICG, GC@ICG based phototherapy was evidenced to suppress lung metastasis and enhance infiltration of CD8+ T cells in untreated distant tumors. Therefore, this design shows promise in addressing the challenges of the treatment of TNBC.